A scoping review of the factors affecting work–life balance among nurse educators - Letta Mathebula; Rirhandzu F. Mathevula; Tshiamo N. Ramalepa (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2025)
Background: There is a dearth of research on the factors that contribute to a lack of work–life balance (WLB) among nurse educators because most studies focused on nurses or academics in general rather than nurse educators. Thus, more studies are needed to explore the factors that contribute to the lack of WLB among nurse educators.